Reverberation times and reverberation levels - PEUTZ, V. M. A. (Archives of Acoustics, 1985)
Reverberation times and reverberation levels are the statistical parameters of the stochastical sound field in a room. Their theoretically derived and practically measured properties are discussed. Reverberation times and reverberation levels are place dependent, they are also to a certain extent influenced by the shape of the hall and the distribution of the absorption in it. This influence is however limited as regards the reverberation times.